International Service-Learning for forest fire management and employability in higher education: a qualitative research - Glenda Galeotti; Chiara Clemente (Firenze University Press, 2023)
The paper introduces exploratory research that examines the effects of participation in interdisciplinary and international service-learning in forest fire management. Service-learning was interpreted as an educational device capable of supporting employability pathways within higher education. This theoretical proposition informed qualitative research that collected students' perceptions of their service-learning experience. The research findings confirm the positive relationship between service-learning participation and the development of key soft skills. Moreover, the findings indicate how service-learning participation fosters labor market knowledge and skills, and opportunities for identifying and exploring academic and professional opportunities and cultivating authentic relationships.   Service-Learning internazionali per la gestione degli incendi boschivi e l'employability nell'alta formazione: una ricerca qualitativa. Il contributo presenta una ricerca esplorativa che esamina gli effetti di partecipazione a progetti di service-learning interdisciplinari e internazionali sulla prevenzione degli incendi. Il service-learning è qui interpretato come un dispositivo educativo capace di sostenere percorsi di employability all'interno di contesti europei di alta formazione. Questa prospettiva teoretica è il punto di avvio di questa ricerca qualitativa che ha raccolto le percezioni degli studenti sull'esperienza di service-learning a cui hanno partecipato. I risultati dello studio confermano il rapporto positivo tra la partecipazione al service-learning e lo sviluppo di soft skills. Viene inoltre rilevato come questa partecipazione possa favorire l'acquisizione di conoscenze e competenze sul mercato del lavoro, per identificare ed esplorare opportunità accademiche e professionali post-laurea e coltivare relazioni autentiche utili alla pianificazione continua del proprio percorso professionale e personale.